2022
DOI: 10.1186/s13690-022-00850-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Campylobacter infections among children of 0–24 months of age in South Africa

Abstract: Background Campylobacter spp. are one of the most frequent causes of diarrhoeal disease in humans throughout the world. This study aimed at determining the prevalence and the genotypic distribution of Campylobacter spp. and their association with diarrhoea and child growth in children of less than the age of two in the Limpopo Province of South Africa. Methods A total of 4280 diarrheal and non-diarrheal stool samples were collected on a monthly bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…The official data on the incidence of cases is limited which impacts the disease epidemiology. Reports show that the prevalence of C. jejuni in developing countries is common in toddlers [ 11 ] which is a concern. The World Health Organization (WHO) reports that Campylobacter infections in toddlers occasionally lead to death [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The official data on the incidence of cases is limited which impacts the disease epidemiology. Reports show that the prevalence of C. jejuni in developing countries is common in toddlers [ 11 ] which is a concern. The World Health Organization (WHO) reports that Campylobacter infections in toddlers occasionally lead to death [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ecuador, the prevalence of this bacterium in healthy children was 13.4% [ 60 ]. Samie et al in South Africa showed the prevalence of Campylobacter in children with diarrhea (13.2%) and without diarrhea (12.4%) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Moreover, it is a principal cause of food-borne infection. 12 Campylobacter jejuni is the most commonly isolated Campylobacter species, which causes human gastroenteritis. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%